Intramolecular oxidative cyclodehydrogenation route for the synthesis of strap-like conjugated polymers. Issue 18 (8th February 2017) - Yang, Junwei; Huang, Wei; Lin, Tingting; Pan, Xiaoyong; Zhu, Haoyun; Huang, Yuli; Wang, Weizhi
Abstract : Based on tetraphenylethene (TPE), a bottom-up solution-based synthesis of narrow strap-like polymers was successfully achieved by intramolecular oxidative cyclodehydrogenation. Abstract : Strap-like conjugated polymers, as the promising materials with opening band gaps, are being rapidly developed for future electronic devices. A bottom-up solution-based synthesis of two novel narrow strap-like polymers on the nanometer scale was successfully achieved by intramolecular oxidative cyclodehydrogenation, and two synthesized polymer precursors were converted via palladium-catalyzed Suzuki–Miyaura polymerization. In comparison, the strap-like polymer, which has more extended conjugation, exhibits better electron transmission and planarization owing to its greater electron delocalization. Owing to their excellent thermal stability and conducting properties, these structurally well-defined nanoribbons were utilized in top-gate field-effect transistors via direct solution processing. The fabricated devices could function well in lower-voltage operations (<5 V) and displayed high performance, with mobilities of about 0.38 cm 2 V −1 s −1 at an on–off ratio of 3.67 × 10 3 and 0.48 cm 2 V −1 s −1 at an on–off ratio of 6.25 × 10 3 .